2019
DOI: 10.4103/sjg.sjg_290_18
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 family members are associated with fast-growing hepatocellular carcinoma and patient survival: An integrated analysis of gene expression profiles

Abstract: Background/Aims: The biological heterogeneity of hepatocellular carcinoma (HCC) makes prognosis difficult. Although many molecular tools have been developed to assist in stratification and prediction of patients by using microarray analysis, the classification and prediction are still improvable because the high-through microarray contains a large amount of information. Meanwhile, gene expression patterns and their prognostic value for HCC have not been systematically investigated. In order to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Finally, survival analysis was performed to explore the potential prognostic value of 289 DEGs, and we identified 12 TME-related genes that showed significant correlation between gene expression and poor outcomes in HCC cases. Of the 12 genes, five genes ( CD80 , IL11 , MMP7 , MMP12 , and PTGIS ) have been reported to be associated with HCC's progression or significant in HCC survival prediction [3742], indicating that our big data analysis based on ESTIMATE algorithm has prognostic values in the HCC cohort of TCGA database. The other seven genes have never been reported to correlate with HCC development and prognosis before and can be perceived as potential biomarkers for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, survival analysis was performed to explore the potential prognostic value of 289 DEGs, and we identified 12 TME-related genes that showed significant correlation between gene expression and poor outcomes in HCC cases. Of the 12 genes, five genes ( CD80 , IL11 , MMP7 , MMP12 , and PTGIS ) have been reported to be associated with HCC's progression or significant in HCC survival prediction [3742], indicating that our big data analysis based on ESTIMATE algorithm has prognostic values in the HCC cohort of TCGA database. The other seven genes have never been reported to correlate with HCC development and prognosis before and can be perceived as potential biomarkers for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…and its expression is correlated with the histological grade of the tumors [ 31 ]. Liu et al [ 32 ] also reported that the risk signature of cytochrome P450 can be used for prognosis of HCC patients. Besides, Hu et al [ 33 ] reported that glycolysis plays an important role in HCC progression by providing sufficient energy to meet energy demands for the rapidly proliferating HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The main function of cytochromes is to detoxify chemicals that could be harmful to tissues. However, this detoxification may produce harmful metabolites that could disrupt the hepatic cellular DNA division mechanisms required to maintain hepatic cellular proliferation, with subsequent cancer formation [ 6 , 7 , 8 , 9 , 10 , 11 ]. Because HCC is a vascularized tumour, we hypothesized that the byproducts of CYP450, including different volatile organic compounds (VOCs), would be found in the urine following the homeostatic HCC cells’ secretion of these compounds into systemic circulation, and subsequent kidney filtration.…”
Section: Introductionmentioning
confidence: 99%